Application of Active Cough Techniques in Cases of Ineffective Airway Clearance in An.Q Patients with a Diagnosis of Acute Bronchopneumonia - Qaimah, Silatil; Munir, Zainal; Dewi, Novela Eka Candra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Background: Bronchopneumonia can disrupt the function of the respiratory tract in the human body, which will later cause clients to experience symptoms of coughing up phlegm, shortness of breath, and can trigger accumulation of secretion production in the bronchial area and around the alveoli, resulting in problems with ineffective airway clearance. Objective: of this study is to identify the application of effective cough techniques for cases of ineffective airway clearance in pediatric patients with acute bronchopneumonia in the children's room at Sidoarjo Regional Hospital. Method: the method used in this final scientific work uses a method of providing effective cough techniques to patients with Results: the nursing evaluation based on progress notes shows that, after implementing effective cough techniques for 3 days of meetings, the indicators in the outcome criteria were fully achieved as evidenced by a decrease on sputum production, additional breath sounds and anxiety felt by the client, as well as improvement in respiratory frequency. Conclusion: The application of the cough technique is effective in overcoming airway clearance problems in pediatric patients with acute bronchopneumonia in the children's room at Sidoarjo Regional Hospital.